Impact Resistance Behaviour of Light Weight Rice Husk Concrete with Bamboo Reinforcement - Muda Z.C.; Beddu S.; Syamsir A.; Ating J.S.; Mohd Kamal N.L.; Mustapha K.N.; Thiruchelvam S.; Usman F.; Alam M.A.; Birima A.H.; Zaroog O.S. (Institute of Physics Publishing, 2023)
Bamboo; Concrete slabs; Concretes; Cracks; Drops; Light weight concrete; Reinforcement; Bamboo reinforcement; Crack resistance; Drop weight impact; Light weight; Linear relationships; Low impacts; Projectile tests; Slab thickness; Concrete reinforcements; bamboo; concrete; crack; diameter; impact; reinforcement; research work; rice; slab; weight